An Overview of Cellulose‐Based Nanogenerators. Issue 3 (1st February 2021) - Annamalai, Pratheep K.; Nanjundan, Ashok Kumar; Dubal, Deepak P.; Baek, Jong‐Beom
Abstract: Developing nanogenerators (NGs) is achieved by exploiting the piezoelectric, triboelectric, and pyroelectric effects of both organic and inorganic materials. Many exhibit beneficial electrical properties (dielectric, conductive, or insulating) or have surfaces that are polarizable upon friction or physical contact. Recently, biomass‐derived materials and recycled materials, whose electrical activity can be induced, are explored for application in the design of more sustainable, cost‐effective, biodegradable, disposable NGs, and have demonstrated a wide range of output (microenergy) power densities. Among them, cellulose, the most abundant biopolymer, is found to offer excellent opportunities for designing and manufacturing NGs with multifunctional capacities. Cellulose can be derived into varied forms with multifunctionalities and physical morphologies. This account provides an overview of how cellulose is utilized in creating NGs based on piezoelectric, triboelectric, and pyroelectric effects. Because the mechanical properties of cellulose are tunable, current research trends on NGs originate with the triboelectric effect. The discussion here focuses on design, fabrication methods, achievable electrical power output, and combinations with other materials and devices. Challenges in efficient fabrication and consistent power densities, and opportunities for integrating different technologies and developing more sustainable (in terms of economic, environmental, and ecological) nature–human–machine interfacial devices are also discussed. Abstract : Nanogenerators utilizing sustainable materials and energies will enable the next generation of cost‐effective technologies for energy harvesting, self‐powered monitoring, and integration in the Industry 4.0 revolution. This overview provides the recent progress on nanogenerators (NGs) utilizing the most abundant biopolymer "cellulose." By comparing the harnessed energy outputs using NGs through piezoelectric, triboelectric, and pyroelectric effects, it also discusses the versatility and new functions that cellulose can offer.